Lip Cosmetics – A Formulator (OR) An innovator to Overcome a Challenge in Quest of Research with its Advances (Asian Journal of Pharmaceutics (AJP), 2024)
Cosmetics which are the Greek origin word have been used by people either knowing or unknowingly in their daily life sinceB.C for maintaining good hygiene, attraction, and beautifying purpose which from the materials or items available fromnatural or other forms of sources from nature. Various classifications on the term cosmetic have been emerged on its usage,form, and application available sources. The various types of cosmetics used for hair hair, skin, tooth, etc., are mostlyavailable in the form of solid, liquid, gas and semisolids with various consistencies for longer duration of action andspecific area of application. Face cosmetics especially lip cosmetics play a significant role in beautifying the entire humanpersonality in orating the surrounding people on various occasions and in regular life. The lip balms, lip stains, lip liner, lipgloss, lipstick, lip oil, etc. are the lip cosmetics available in the market. To formulate a cosmetic, a great challenging task is toovercome by a researcher or scientist or formulator or innovator because the cost or price of cosmetics is higher than the cost ofother needs of humans the product available or manufactured must win the user with its enrichment or articulate in appearanceby the customer. The selection of ingredients and the method of preparation and its evaluation play an important role in theirfuture marketed product life in its consistency and utility. All lip cosmetics must be formulated using a sufficient amount ofwaxes, oils, antioxidants, preservatives, coloring agents, perfumes, moisturizing agents, and other essential ingredients andmust be properly evaluated for all tests specified such as test on softening point, melting point, stability study test, freedomfrom grittiness and greasiness, test on pH, stability test for perfume, test on surface anomalies and solubility, test on breakingpoint and thixotropy character, test on force of application and skin irritation, lead and other metals limit test, and aging stabilitytest. The marketed products available on lip cosmetics with names of Carmex, Nivea, Blistex, Himalaya lip balm, MaybellineNY Super Stay Matte Ink Liquid, Revlon Ultra HD Matte Lip Mousse, SUGAR Cosmetics Smudge Me Not Liquid Lipstick,Zayn and Myza Liquid Lipstick, FACES Canada Ultime Pro Matte Crayon, Colorbar Sinful Matte Lipstick.